The Monster Under the Bed: Chavismo as a Wedge Issue in Latin America - Sagarzazu, Iñaki; Mouron, Fernando (Revista Latinoamericana de Opinión Pública, 2020)
There is a broad array of literature analyzing the interaction between domestic and foreign policy. In this regard, we have recently seen that strategic politicians use divisive foreign leaders as a tool to take advantage of in domestic politics. Nevertheless, the use of these leaders in domestic campaigns – and particularly the reasons why this occurs – has not received much attention in academia. In this paper, we attempt to approach this topic by identifying when conditions are ripe for this strategic use of foreign leaders in domestic politics. More specifically, we argue that the image of foreign leaders can be used when they present the conditions to become a wedge issue. We explore this question by using survey data on views of Chávez across Latin America together with political and economic indicators between 2005 and 2011. We find that perceptions of Chavismo are divisive in countries in which the incumbent government is ruled by a left-wing administration. Similarly, we show that, in those countries, Chavismo has all the conditions to become a wedge issue, as opponents have a homogeneously negative perception of that political movement, while government supporters are divided in their views of Chavismo.